Adoption of digital dual supply networks by SMES in the Capricorn district of Limpopo Province in South Africa - Sefala, Maite (University of the Witwatersrand, Johannesburg, 2022)
This research investigates the adoption of digital tools, specifically Digital Dual-Supply Networks (DDSN), by Small and Medium Enterprises (SMEs) operating within the Capricorn District of the Limpopo Province in South Africa. As the digital landscape continues to evolve, SMEs face increasing pressure to integrate innovative technologies into their business operations. The study aims to understand the current state of digital tool adoption, the factors influencing adoption decisions, and the impact of DDSNs on the overall performance, sustainability, and growth of SMEs in the region. Thus, four parental concepts, namely, digital dual-supply network, sustainability, growth, and performance of the SMEs are investigated to establish an impact they could have on the SMEs in Limpopo province, South Africa. This study will follow a qualitative research design and data will be collected through interviews to gain comprehensive insights into the dynamics of digital tool adoption within the SME sector. The research will explore the challenges hindering adoption, identify successful cases, and analyse the strategic considerations that influence the decision-making process of SMEs when integrating DDSNs. Moreover, the study will also explore the context of the dual-channel digital supply chain network and its importance in the sustainability of the SMES as well as analysing the concepts of collaboration and digital transformation of Capricorn district SMEs within the ever-changing and market trends and demands. Digital Dual-Supply Networks (DDSNs) represent a paradigm shift in supply chain management, leveraging advanced digital technologies to create more agile and resilient networks. This research not only advances theoretical knowledge in the field but also offers practical implications for businesses contemplating or currently undergoing digital transformation through the adoption of DDSNs. The resulting framework aims to guide organizations in optimizing their supply chain processes, fostering innovation, and adapting to the dynamic landscape of the digital era. The findings of this research will contribute to the existing body of knowledge on technology adoption in SMEs, providing valuable insights for policymakers, business owners, and researchers interested in fostering digital transformation within the Capricorn District and similar regions. Ultimately, the study aims to offer practical recommendations to enhance the adoption of DDSNs among SMEs, promoting their sustainable growth and competitiveness in the ever-evolving digital business landscape. Keywords: SMEs; digitalization, collaboration, dual dual-channel digital supply chain network, sustainability, growth
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2022
Keywords: SMEs; Digitalization; Collaboration; Dual dual-channel digital supply chain network; Sustainability; Growth; UCTD; SDG-8: Decent work and economic growth